Analysis of the Relationship Between Learning Styles and the Level of Critical Thinking Skills of Learners on Global Warming Material in High School - Aji, Dwi Purnomo; Akhsan, Hamdi; Marlina, Leni; Wiyono, Ketang; Kistiono, Kistiono (Berkala Ilmiah Pendidikan Fisika, 2024)
This study aims to determine the relationship between learning styles and the level of thinking skills of students on global warming material in high school. The research method used in this research is descriptive qualitative, involving research subjects as many as 69 students of class X phase E independent curriculum who are available and willing to be studied. The data were analyzed using Cramer's correlation coefficient, PHI correlation coefficient, lambda correlation coefficient, and TAU-B and TAU-C correlation coefficients. The results of the analysis are the Chi-Square count of the Cramer correlation coefficient, which is (14.399) > Chi-Square table (5.591), the Chi-Square count of the PHI correlation coefficient is (6.534) > Chi-Square table (3.841), the Chi-Square result of the lambda correlation coefficient is (38.687) > Chi-Square table (9.448), and the Chi-Square result of the TAU-B and TAU-C correlation coefficient is (33.051) > Chi-Square table (9.448). This means there is a significant correlation between students' learning styles and critical thinking skills on global warming material in high school, and the correlation coefficient still shows a reasonably strong interpretation. Students who have auditory and visual learning styles tend to have a higher level of critical thinking skills than students who have kinesthetic learning styles. This shows that there is a reasonably strong relationship between learning styles and critical thinking skills of students on global warming material in high school.